High-grade high-dysplastic lumbosacral spondylolisthesis in children treated with complete reduction and single-level circumferential fusion: A prospective case series - Štulík, Jan; Geri, Gábor; Barna, Michal; Klézl, Zdeněk (Brain & spine, 2022)
INTRODUCTION: Surgical treatment of high-grade developmental spondylolisthesis remains controversial with paucity of data reporting complete reduction of the deformity, especially in pediatric patients. RESEARCH QUESTION: To assess efficacy and safety of complete reduction and circumferential L5-S1 fusion in children with high-grade high-dysplastic spondylolisthesis. Emphasis was placed on fusion rates, correction of lumbosacral deformity and long-term clinical outcomes by means of patient-reported outcome measures (PROMs). MATERIAL AND METHODS: Consecutive series of 18 pediatric patients referred to surgery over an 11-years period. Several radiographic variables and PROMs were collected pre- and post-surgery with minimum follow-up of 2-years. RESULTS: The mean age of cohort was 12.9 years with a mean follow-up of 7.8 years. Postoperatively, the mean slip was reduced from 64.4±9.8% to 4.5±5.9% with no loss of correction during follow-up. PROMs significantly improved following the index procedure (p<0.0001). Lumbo-pelvic parameters improved after surgery, including SS, but not PT. Development of adjacent level spondylolisthesis was noted in eight subjects (44%), two of these patients required additional surgery. Posterolateral and anterior fusion was obtained in 100% and 78% of cases, respectively. One patient developed a transient right-sided L5 nerve paresis after surgery that gradually resolved within one year post-surgery. Preoperatively, we recorded three patients with L5 nerve root motor deficit, which resolved completely in two cases and in one patient remained unchanged. DISCUSSION AND CONCLUSION: Complete reduction can safely be accomplished without an increased risk of nerve root injury. Coupled with single-level circumferential fusion, it provides high fusion rates with satisfactory spino-pelvic alignment.